2015
DOI: 10.1007/s11259-015-9634-5
|View full text |Cite
|
Sign up to set email alerts
|

Heart rate deflection point during incremental test in competitive agility border collies

Abstract: The aim of this study was to determine a heart rate deflection point (HRdp) in competitive agility dogs. Fourteen healthy border collies underwent progressive incremental treadmill exercise--modified Conconi test protocol. Heart rate was continuously recorded, and the HRdp was estimated using two methods: subjective and computer aided regression. Maximal heart rate (HRmax), achieved running speed at the anaerobic threshold and at the end of test were also determined. Statistical analysis showed a very high pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
35
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(40 citation statements)
references
References 20 publications
3
35
2
Order By: Relevance
“…In the present study, HR was used as an indicator to verify the primary effect of continuous and interval exercise programs in Beagles. e average maximum HR in canines during progressive exercise testing reported in the previous study was 230 bpm [37], while in the current study, it was 223 bpm. e data indicated that the continuous and interval exercise programs are submaximal and may show a positive impact on cardiovascular fitness in all Beagles.…”
Section: Discussioncontrasting
confidence: 53%
“…In the present study, HR was used as an indicator to verify the primary effect of continuous and interval exercise programs in Beagles. e average maximum HR in canines during progressive exercise testing reported in the previous study was 230 bpm [37], while in the current study, it was 223 bpm. e data indicated that the continuous and interval exercise programs are submaximal and may show a positive impact on cardiovascular fitness in all Beagles.…”
Section: Discussioncontrasting
confidence: 53%
“…Lactate was not shown to be correlated with heart rate in this study, but was directly correlated with increasing RR and temperature. This lack of demonstrable correlation with heart rate may be due to a failure to reach the heart rate deflection point (the conversion from predominately aerobic to predominately anaerobic exercise) (Grazzi et al 2005, Bodner & Rhodes 2012, Faude et al 2012, Radin et al 2015. It may also be due to a delay in a significant lactate rise, which may not have been captured during our sampling times.…”
Section: Discussionmentioning
confidence: 89%
“…, Radin et al . ). It may also be due to a delay in a significant lactate rise, which may not have been captured during our sampling times.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Numerous studies have been performed evaluating the physiological effects of exercise on the body in humans, horses, and dogs. (Fazio et al 2003;McGowan and Hampson 2007;Millard 2014;Gillette and Dale 2014;Perrino et al 2011;Timothy I. Musch et al 1985;McClelland et al 1995;Piccione et al 2012;Rathore et al 2011;Mukai et al 2010;Tipton and Wolfe 1998;Escribano et al 2013;Miura et al 1994;Radin et al 2015;Poole and Erickson 2011;Faude, Kindermann, and Meyer 2012;Steiss et al 2004;Srđan et al 2013;Conconi et al 1996;Grazzi et al 2005;Ferasin and Marcora 2009;Pasławska et al 2012;Treiber et al 2010;Crook, Wilson, and Hodson-Tole 2010;Scott et al 2010;McCauley et al 2013;T. I. Musch et al 1987; Bartolomé et al 2013;Ramseyer et al 2010;Rathore et al 2010;McCutcheon and Geor 2010) It has been well documented that heart rate, respiratory rate, rectal temperature, oxygen uptake (VO2), blood lactate concentration, red blood cell (RBC) concentration, and hematocrit (HCT) all generally increase with increasing intensity of exercise, while glucose concentrations generally decrease.…”
Section: Introductionmentioning
confidence: 99%